2021
DOI: 10.1101/2021.11.23.469669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha oscillations and stimulus-evoked activity dissociate metacognitive reports of attention, visibility and confidence in a rapid visual detection task

Abstract: Variability in the detection and discrimination of weak visual stimuli has been linked to prestimulus neural activity. In particular, the power of oscillatory activity in the alpha-band (8-12 Hz) has been shown to impact upon the objective likelihood of stimulus detection, as well as measures of subjective visibility, attention, and decision confidence. We aimed to clarify how prestimulus alpha influences performance and phenomenology, by recording simultaneous subjective measures of attention and confidence (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Thus far, only a few studies have directly investigated the CPP's relationship with confidence and these have yielded apparently mixed results. While several studies have reported positive relationships between pre-choice CPP amplitude and confidence (Davidson et al, 2021;Gherman & Philiastides, 2015Herding et al, 2019;Pereira et al, 2021;Tagliabue et al, 2019), two studies found no such relationship (Feuerriegel et al, 2022;Rausch et al, 2020) .…”
Section: Introductionmentioning
confidence: 83%
“…Thus far, only a few studies have directly investigated the CPP's relationship with confidence and these have yielded apparently mixed results. While several studies have reported positive relationships between pre-choice CPP amplitude and confidence (Davidson et al, 2021;Gherman & Philiastides, 2015Herding et al, 2019;Pereira et al, 2021;Tagliabue et al, 2019), two studies found no such relationship (Feuerriegel et al, 2022;Rausch et al, 2020) .…”
Section: Introductionmentioning
confidence: 83%
“…Alternatively, a quadratic modulation of decision confidence may reflect object-level (that is, not meta-level) inter-trial fluctuations in visual attention. As an example of how this might arise, a recent EEG study [ 27 ] revealed a negative linear relation between reported attention and pre-stimulus alpha power in the 8–12 Hz frequency band. By contrast, high levels of decision confidence were associated with intermediate pre-stimulus alpha power, giving rise to a negative quadratic relation between alpha power and confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a quadratic modulation of decision confidence may reflect object-level (that is, not meta-level) inter-trial fluctuations in visual attention. As an example of how this might arise, a recent EEG study (Davidson et al, 2021) revealed a negative linear relation between reported attention and pre-stimulus alpha power in the 8-12 HZ frequency band. In contrast, high levels of decision confidence were associated with intermediate prestimulus alpha power, giving rise to a negative quadratic relation between alpha power and confidence.…”
Section: A Quadratic Modulation Of Confidence: Ideas and Speculationsmentioning
confidence: 99%